Hypotension prediction index for minimising intraoperative hypotension: A systematic review and meta-analysis of randomised controlled trials - Kamath Sriganesh; Thomas Francis; Rajeeb Kumar Mishra; Nisarga N Prasad; Dhritiman Chakrabarti (Indian Journal of Anaesthesia)
Background and Aims: Reports on the utility of the hypotension prediction index (HPI) in reducing the occurrence of intraoperative hypotension are conflicting. Therefore, the aim of this systematic review and meta-analysis of randomised controlled trials (RCTs) was to evaluate the overall effect of using HPI on intraoperative hypotension outcomes of time-weighted average (TWA), area under the hypotension threshold (AUHT), incidence and duration of hypotension. Methods: We searched the electronic databases of PubMed, ProQuest and Scopus from inception till 30 October 2023. The search strategy was refined for each database. No time or language restrictions were applied. Only RCTs were included. The systematic review protocol is registered with PROSPERO (ID: CRD42023478150). Statistical analysis was performed using Review Manager Software. Results: Of 281 records, eight eligible RCTs (613 patients) were included. Significant differences were found between HPI and no HPI groups for the TWA of hypotension during surgery [mean difference (MD) = -0.19 mmHg, 95% confidence interval (95% CI): -0.31, -0.08, P = 0.001], AUHT [MD = -65.03 (mmHg × min), 95% CI: -105.47, -24.59, P = 0.002], incidence of hypotension (risk ratio = 0.83, 95% CI: 0.7, 0.99, P = 0.04), total hypotension duration (MD = -12.07 min, 95% CI: -17.49, -6.66, P < 0.001) and hypotension duration as a percentage of surgery time (MD = -6.30%, 95% CI: -10.23, -2.38, P = 0.002). Conclusions: Available evidence supports the role of HPI in minimising hypotension outcomes during surgery. The certainty of evidence is low to moderate for studied outcomes.